Analisis Risiko Keselamatan Dan Kesehatan Kerja (K3) Pada Proses Perbaikan Kapal di PT. Dock Dan Perkapalan Surabaya Menggunakan Metode Hirarc (Hazard Identification, Risk Assessment, And Risk Control) - Johin Dava Fairussihan; Dwisetiono (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2022)
The shipping industry or shioyard is acompany engaged in shp construction and repair , and is a strategic sector has a vital role for the national ecobomy. PT Dock Dan Perkapalan Surabaya is a company engaged in the construction and repair of ship based in Tanjung Perak Surabaya. Occupational heath and safety or K3 is the most important a aspect in all shipbuilding activities to ensure and protect the safety and health of workers throught efforts to prevent work accidents and occuptional diseases. The risk of work accidents in large shipyards ranging from minor to serious a accidents. The purpose of this study was to determine hazard identification, risk assessment, and risk control using the hazard identification, risk assessment, and risk control (HIRARC)